2003
DOI: 10.1046/j.1466-7657.2003.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of hospital nurses: an empirical test of a causal model in Taiwan

Abstract: It is suggested that having information on a nurse's personality will help to predict her/his future job satisfaction and may lead to improved selection of personnel. In addition, different management styles or reward systems that are sensitive to different personalities should be carefully studied and implemented, as appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
2
35

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 25 publications
7
63
2
35
Order By: Relevance
“…The current study supports the assertion from Chu et al (2003) that the clinical specialty should be investigated in more detail when looking at job satisfaction. This study showed that the clinical specialty explains additional variance in job stress and satisfaction beyond Karasek"s model and self-efficacy.…”
Section: Discussion Related To Incidental Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…The current study supports the assertion from Chu et al (2003) that the clinical specialty should be investigated in more detail when looking at job satisfaction. This study showed that the clinical specialty explains additional variance in job stress and satisfaction beyond Karasek"s model and self-efficacy.…”
Section: Discussion Related To Incidental Findingssupporting
confidence: 88%
“…The current sample had a higher percentage of baccalaureate prepared nurses than previous research had found. There is evidence that educational preparation impacts negatively on job satisfaction of nurses (Blegen, 1993;Chu et al, 2003), but there is some inconsistency and the direction of the relationship is not clear (Coomber & Barriball, 2007). For this reason also, caution needs to be taken in generalizing of the results of the current study.…”
Section: Limitations Of the Studymentioning
confidence: 70%
See 1 more Smart Citation
“…Organizations cannot succeed without their personnel efforts and commitment (A Mohamood& M Hossain, 2006). Than organization considered and used many tools for employee job satisfaction such as: salaries, achievement, job security and workplace flexibility (Koustelios et al, 2003;Navaie-Waliser et al, 2004;Ilies and Judg, 2003;Gigantesco et al, 2003;McNeese-Smith, 1999;Blegen, 1993;De Loach, 2003;Chu et al, 2003;Thyer, 2003). Number of the researches pointed that the teacher self efficacy having a impact on student achievement and success (Moore &Esselman, 1992Muijs&Rejnolds, 2001;Ross, 1992.The opportunities for individual and specialized development and achievement is one of the most excellent predictors of job satisfaction (Lyons et al, 2003;Al-Ahmadi, 2002;Freeborn and Hooker, 1995;Wittig et al, 2003).…”
Section: H1: Job Security Has a Positive Effect On Job Satisfactionmentioning
confidence: 99%
“…개인의 특성과 직무만족 간의 관계 또는 조직 의 근무환경과 직무만족 간의 관계에 대한 선행연구는 개인적 특성이 직무만족에 영향을 미치며 (Kim & Yoon, 2011;Lee & Kwon, 2011;Yoon & Cho, 2007), 근무환경 및 조직특성 역시 직무만족도와 상관 관계가 있으며 (Bonner & Pryor, 2010;Chu, Hsu, Price & Lee, 2003;Hayes, Adams & Bond, 2000;Kim & Hwang, 2011), 종사자들의 직무만 족은 서비스 질에 긍정적 영향을 미친다고 하였다 (Choi, 2008;Oh, 2008;Scotti, Harmon & Behson, 2007 …”
unclassified